Errorless learning and rehabilitation of language and memory impairments : a special issue of the journal Neuropsychological Rehabilitation - Conroy, Paul; Lambon Ralph, Matthew A (London : Routledge, 2013)
This book brings together seven newly published studies from a range of invited international researchers in the fields of language and memory disorders and their rehabilitation. The studies address a range of current themes within these fields. Critical consideration is made of the concept of errorless learning in light of the current learning literature. The breadth and depth of these studies offers an up-to-date and comprehensive account of research developments in errorless learning and rehabilitation of language and memory impairments. They delineate some of the current critical theoretical-clinical issues through which we might optimise learning and rehabilitative efforts more fully.
Machine generated contents note: 1.Introduction: Errorless learning and rehabilitation of language and memory impairments / Matthew A. Lambon Ralph -- 2.Errorless learning in cognitive rehabilitation: A critical review / Myrna F. Schwartz -- 3.Contributions of frontal and medial temporal lobe functioning to the errorless learning advantage / Linda Clare -- 4.Quest for the best: Effects of errorless and active encoding on word re-learning in semantic dementia / Nicole D. Anderson -- 5.A direct comparison of errorless and errorful therapy for object name relearning in Alzheimer's disease / Matthew A. Lambon Ralph -- 6.Contrasting effects of errorless naming treatment and gestural facilitation for word retrieval in aphasia / Colleen Casselton -- 7.Error reduction therapy in reducing struggle and grope behaviours in apraxia of speech / Rosemary A. Varley -- 8.Decreasing cues for a dynamic list of noun and verb naming targets: A case-series aphasia therapy study / Jade Scowcroft -- 9.Overview and ways forward for future research / Matthew A. Lambon Ralph.
Includes bibliographical references and index.
Keywords: Clinical neuropsychology; Language disorders -- Patients -- Rehabilitation; Memory disorders -- Patients -- Rehabilitation; Cognitive neuroscience; Learning, Psychology of